2010
DOI: 10.1111/j.1469-0691.2009.03125.x
|View full text |Cite
|
Sign up to set email alerts
|

Legionnaires’ disease caused by Legionella longbeachae and Legionella pneumophila: comparison of clinical features, host-related risk factors, and outcomes

Abstract: Legionnaires' disease remains an important cause of mortality and morbidity worldwide. Disease caused by Legionella pneumophila has been extensively studied, and its clinical characteristics have been well described. There is, however, little information on disease caused by Legionella longbeachae, despite its importance in some countries. We undertook a retrospective review of culture-positive cases of Legionnaires' disease in the Canterbury region of New Zealand over 10 years, in order to compare the clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 16 publications
3
25
2
1
Order By: Relevance
“…Significantly more L. pneumophila-infected patients reported breathlessness, but no differences were observed in any other pre-hospital symptoms. These results are consistent with the findings of the aforementioned New Zealand study that found little difference in clinical features between cases of L. longbeachae and L. pneumophila (Amodeo et al, 2010). Most cases in both groups had a date of onset in the spring or summer months (March to August), and there was no significant difference in the time of year of onset for cases.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Significantly more L. pneumophila-infected patients reported breathlessness, but no differences were observed in any other pre-hospital symptoms. These results are consistent with the findings of the aforementioned New Zealand study that found little difference in clinical features between cases of L. longbeachae and L. pneumophila (Amodeo et al, 2010). Most cases in both groups had a date of onset in the spring or summer months (March to August), and there was no significant difference in the time of year of onset for cases.…”
Section: Resultssupporting
confidence: 82%
“…This is consistent with an early Australian study (Cameron et al, 1991), but differs from the results of a New Zealand study comparing L. longbeachae with L. pneumophila cases which found no difference in smoking status between cases (Amodeo et al, 2010). Half of the individuals infected with L. longbeachae were treated in intensive care, which was significantly more than the 12 % (95 % CI 0-25 %) of L. pneumophila cases.…”
Section: Resultssupporting
confidence: 33%
“…This is also a similar characteristic of legionellosis epidemiology in the Northern Hemisphere to some degree ; however, the seasonality appears to be summer-autumn, possibly a reflection in recent years of warmer and humid weather [32]. Such seasonal trends in New Zealand may suggest a greater seasonal influence on environmental reservoirs such as gardening potting mix and compost which may influence the degree of human risk [33]. Legionella populations in cooling towers are also likely to be well established after the summer period [31].…”
Section: Discussionmentioning
confidence: 95%
“…For the species L. longbeachae two serogroups are described to date (Bibb et al, 1981; Mckinney et al, 1981). L. longbeachae Sg1 is predominant in human disease as it causes up to 95% of the cases of legionellosis worldwide and most outbreaks and sporadic cases in Australia (Anonymous, 1997; Montanaro-Punzengruber et al, 1999). The two main human pathogenic Legionella species, L. pneumophila and L. longbeachae cause the same disease and symptoms in humans (Amodeo et al, 2009), however, there exist major differences between both species in niche adaptation and host susceptibility.…”
Section: Introductionmentioning
confidence: 99%